TINJAUAN PENGADAAN LINEN KAMAR OLEH LAUNDRY SECTION PADA SAAT HIGH OCCUPANCY DI HOTEL HILTON BANDUNG - Fatimah Azzahra; Della Sari, Windy; Polisda, Yen (Jurnal Pariwisata Bunda, 2023)
This article reports the results of research on the handling of room linen in an effort to parstock linen by the laundry section. This study used a descriptive method, with data collection techniques through observation of room linen handling and interviews about the parstock of room linen with the laundry at Hotel Hilton Bandung. The results showed that  the handling of room linen in the laundry section of Hotel Hilton Bandung has run well and smoothly starting from controlling linen, handling damaged linen, replacing dirty and clean linen, to handling linen when high occupancy occurs. Then during high occupancy, laundry conducts the open store option by issuing new linen stock, so that it can overcame the shortage of linen when high occupancy occurs